PENGARUH PENGGUNAAN MODEL PEMBELAJARAN MANDIRI TERHADAP KEMAMPUAN BERPIDATO SISWA KELAS IX.A SMP NEGERI 15 BULUKUMBA - Arsan, Wiwik; Ramly, Ramly; AJ, Andi Agussalim (Universitas Negeri Makassar, 2024)
This study aims to describe the ability of speech before using independent learning model, the ability after using independent learning model, and the effect of using independent learning model on students' speech ability. The method used in this research is quantitative method, the research design used is One Group Pretest-Posttest Design. The population in this study was Class IX students of SMP Negeri 15 Bulukumba, totaling 37 students. The sampling used was using purposive sampling technique. The sample in this study amounted to 19 students. The data collection technique in this study was speech task. The collected data were analyzed with descriptive statistics and inferential statistics. The results of data analysis show that the use of independent learning models can affect students' speech skills. The results of hypothesis testing showed that the sig value. 0.038 <0.05 so that the alternative hypothesis (Ha) is accepted, namely there is an effect of the use of independent learning models on students' speech skills.